Perencanaan Ruang Bakar Fluidisasi Menggunakan Bahan Bakar Sampah - Barita; Eswanto; Kirfan Wujud (CV. IRA PUBLISHING, 2022)
The need for energy is now increasing in line with the development of human and economic growth. If you only rely on fossil energy, the needs in the next few years will greatly impact the balance of natural resources. Along with the development of the times and followed by the depletion of fossil resource reserves which have been energy throughout the world, it has given birth to many technologies for converting renewable natural resources as an effort to emphasize the use of fossil fuels. One such technology is a fluidized bed combustor (FBC). This study explains the use of waste fuel which can be used as fluidization combustion chamber planning. In designing the number of holes and the diameter of the holes, the distributor type of perforated plate is very good at distributing air flow to the sand bed for the fluidization process. The difference due to the height of the sand can be seen in the sand height of 3 cm, it takes 16 minutes to carry out the preheating process, 4 cm the height of the sand takes 18 minutes to preheating and the sand height of 5 cm takes 21 minutes to carry out the preheating process. So it can be seen, the higher the sand, the longer the preheating process but the heat storage process on the bed is better.